Notary Disclaimer Of Coastal Lands On The Development Of Legal Resort - La Ode Arsanudin (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to analyze the regulation of coastal land, the role of the notary in the release of coastal land rights to resort development bodied laws and What are the constraints and solutions in the relinquishment of coastal land titles to resort development who are legally incorporated in Wakatobi Regency, Southeast Sulawesi Province. This study uses an empirical juridical approach, the types and sources of data in this study are primary data and secondary data as well as tertiary data, legal materials and data obtained through literature studies and field surveys with study and interview collection tools, Wakatobi district research area, analysis techniques. data based on qualitative analysis. System The zoning for Wakatobi National Park refers to the Minister of Forestry Regulation Number: P.56 / Menhut-II / 2006 dated 29 August 2006 regarding the Guidelines for National Park Zoning. For the involvement of the Notary, it is not only to help the process of making the deeds of the Waiver of Rights or APH also cares about the waiver process carried out by the parties who are its clients and are willing to provide guidance / advice and legal consultation related to the waiver of rights or problems land in general and it is also known that there is a lack of socialization to the community regarding the zoning system in effect in Wakatobi Regency.